Risk of cardiovascular disease and death in patients with breast cancer receiving anthracycline-based therapy: A retrospective cohort study - Yu-Cheol Lim; Yoon Jae Lee; In-Hyuk Ha; Ye-Seul Lee (PLoS ONE, 2025)
Background With the increasing survival rate and overall lifespan of patients with breast cancer, increased mortality due to cardiovascular causes is a notable concern. Anthracyclines, which are commonly used and effective chemotherapeutic agents for breast cancer, are known for their cardiotoxicity. Existing studies vary in their findings owing to heterogeneous factors such as study population and design, underscoring the need for high-quality evidence to comprehensively examine the risk factors for anthracycline-induced cardiotoxicity. This study compared the incidence of cardiovascular disease, all-cause mortality, and their associated risk factors following adjuvant anthracycline therapy as the initial anticancer treatment, utilizing National Health Insurance claims data for a nationwide cohort of patients with breast cancer. Methods The study cohort comprised patients initially diagnosed with breast cancer between 2011 and 2013 who underwent mastectomy within 6 months of diagnosis and received anticancer therapy within 6 months of surgery. The primary outcomes were composite cardiovascular events and all-cause mortality during a follow-up period of up to 5 years. Secondary outcomes encompassed specific types of cardiovascular events such as congestive heart failure, heart failure and cardiomyopathy, coronary artery disease and cardiac arrest, and stroke. Incidence rates for these outcomes were presented as incidence rate ratios (IRR), and hazard ratios (HR) for individual risk factors were derived using the Cox proportional hazards model. Results The study cohort comprised 9,439 patients with breast cancer in both the anthracycline and non-anthracycline groups. There was no significant association between adjuvant anthracycline therapy and the composite cardiovascular events (adjusted HR 0.911 [95% CI 0.823–1.008]). In contrast, all-cause mortality was higher in the anthracycline group (IRR 2.155 [95% CI 1.892–2.455]; adjusted HR 2.160 [95% CI 1.882–2.480]). Adjuvant trastuzumab was significantly associated with an increased risk of the composite cardiovascular event (adjusted HR 1.256 [1.093–1.443]), although no trend was identified concerning adjuvant trastuzumab status in the subgroup analysis. Advanced age and hypertensive comorbidities were risk factors for all outcomes. Conclusion To prevent cardiovascular event onset in patients with breast cancer undergoing anthracycline-based chemotherapy, thorough monitoring is essential, especially in patients of advanced age, those with comorbid hypertension, and those undergoing trastuzumab treatment.